Evaluating Hemagglutination Inhibition Antibody Titers as a Correlate of Protection for Influenza: A Sensitivity Analysis Based on Information Theory and Causal Inference - Fenny Ong; Geert Molenberghs; Andrea Callegaro; Wim Van Der Elst; Geert Verbeke; Florian Stijven; Ingrid Van Keilegom; Ariel Alonso Abad (Journal of Global Infectious Diseases)
Introduction: Identifying hemagglutination inhibition (HI) antibody titers as a key immune correlate of protection (CoP) is crucial for developing, licensing, and monitoring the ongoing effectiveness of new influenza vaccines. Using a new statistical methodology, we explored the link between an inactivated quadrivalent influenza vaccine’s impact on HI antibody titers and its effectiveness against A/H1N1-associated influenza illness. Methods: We utilized data from a phase 3, observer-blind, randomized, controlled trial in children aged 6–35 months to assess HI antibody titers as an immune CoP. The assessment used a statistical method developed within a causal inference framework and a new information-theoretic metric of surrogacy, the so-called individual causal association (ICA). Results: The 75% and 85% uncertainty intervals of the ICA are 0.5511–0.8282 and 0.3632–0.8684, respectively, indicating a substantial reduction in the uncertainty about the vaccine’s effect on the absence of infection when its impact on the HI antibody titers is known. Conclusions: The evaluation yielded evidence supporting the validity of HI antibody titers as a CoP for influenza infection.